Probabilitas Tingkat Laba Bursa Efek Indonesia Periode 1 Juli 1997 – 1 Juli 2011 - Tomy G. Soemapradja (Binus Business Review, 2011)
Capital market investor should considers whether the higher expected return, the more risk should be taken, to minimize speculative decision. The research objectives are measuring and describes the probability distribution of market return of IHSG, in July 1, 1997- July 1, 2011, according to availability of public data provided by Indonesian Stock Exchange (IDX). Classification were made with several considered assumptions, results that the largest probability movements of Indonesian Stock Exchange, represented by IHSG percentage of change, is relatively stable of 89,1%, the cumulative probability of downtrend and market crash is 6.3%, whether the cumulative probability of uptrend and booming is 4,6%. This research results the expected return based on probability distribution is 0.049% per day. Assumed 12% pa of time deposits interest rate or 0.033% per day, it means the market risk premium only 0.17% per day or 6% pa. The Capital market is suitable for risk seeker rather than risk averter or risk normal. But risk averter and risk normal may use other alternative instrument such mutual funds when they want to invest their money into capital market.